The use of biomarkers in sepsis: a systematic review - Giannakopoulos, Konstantinos; Hoffmann, Ursula; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim; Behnes, Michael (Current pharmaceutical biotechnology, 2017)
Background: Despite the extended laboratory and clinical study of sepsis, its diagnosis remains a clinical challenge. The initiation of sepsis activates many different biochemical and immunological pathways being expressed by alterations of various molecules in human tissues. The detection and measurement of the concentration of such molecules, known as biomarkers, may be a diagnostic tool of great significance for clinicians dealing with suspected sepsis. Additionally, biomarkers may predict patients ´ outcome and may play a role in monitoring response to therapy. Methods: Most relevant clinical and experimental biomarker studies on sepsis were retrieved and reviewed in this article. Results: Although many biomarkers were evaluated for the diagnosis and prognosis in sepsis, until now not one has been proven to be absolutely reliable in the clinical field. Currently C-reactive proteine (CPR) and procalcitonin (PCT) are used worldwide routinely, nevertheless their values may elevate in clinical settings without sepsis, while they often fail to provide reliable prediction of the patient outcome. Conclusion: This review outlines most relevant circulating biomarkers in sepsis.